Are Recent Peculiar Velocity Surveys Consistent? - Hudson, M; Smith, R; Lucey, JR; Schlegel, D; Davies, R (1999)
We compare the bulk flow of the SMAC sample to the predictions of popular cosmological models and to other recent large-scale peculiar velocity surveys. Both analyses account for aliasing of small-scale power due to the sparse and non-uniform sampling of the surveys. We conclude that the SMAC bulk flow is in marginal conflict with flat COBE-normalized Lambda-CDM models which fit the cluster abundance constraint. However, power spectra which are steeper shortward of the peak are consistent with all of the above constraints. When recent large-scale peculiar velocity surveys are compared, we conclude that all measured bulk flows (with the possible exception of that of Lauer and Postman) are consistent with each other given the errors, provided the latter allow for `cosmic covariance'. A rough estimate of the mean bulk flow of all surveys (except Lauer and Postman) is ~400 km/s towards l=270, b=0.